FREEZE-DRYING KINETICS AND DIFFUSION MODELING OF SAFFRON (CROCUS SATIVUS L.) - Acar, Bahadir; Sadikoglu, Hasan; Doymaz, Ibrahim (WILEY-BLACKWELL, 2015)
The freeze drying is a suitable dehydration process for saffron that contains heat-sensitive volatile and aroma-yielding compounds such as crocin (act as a coloring agent), picrocrocin (responsible for the taste) and safranal (volatile oil that gives characteristic odor and aroma). The heat-sensitive volatile and aroma-yielding compounds of saffron can be more preserved using freeze drying in comparison with other conventional drying methods. In this study the freeze-drying characteristics of saffron was determined experimentally. The drying kinetics data were fitted to 10 different empirical diffusion drying models from literature to find the best model that represents the weight loss of saffron during the freeze drying. Among the models tested in this study, the Page model was found to be the best model in representing the drying kinetics of saffron during the freeze drying. Effective diffusivity found as 1.62x10(-11)m(2)/s. Practical ApplicationsSaffron, which has been intensively used for flavoring and coloring foods, dying textile and medical purposes since ancient times, is the most precious and expensive agricultural product in the world. Freeze drying, which is both slow and expensive, is the method of separation for high market value products. It has been shown that freeze drying can be used for dehydration of saffron with minimum safranal (main aroma component) and crocin (coloring agent) loss. High cost of freeze drying of saffron can be compensated by minimum loss of safranal and crocin contents in the final product. It is crucial to know the drying kinetics of saffron to determine the drying time under certain conditions. In this work, the freeze-drying kinetics of saffron were studied and the best empirical model that represents the weight loss of saffron during the freeze drying and effective diffusivity were determined.
Keywords: DEVELOPMENT NEEDS; SLICES; DRYER; TEMPERATURES; QUALITY; STIGMAS; TRAYS; Food Science & Technology